2002
DOI: 10.1002/ajmg.a.10146
|View full text |Cite
|
Sign up to set email alerts
|

14q(22) deletion in a familial case of anophthalmia with polydactyly

Abstract: We report a family of anophthalmia with ocular and extraocular manifestations. The proband, his three sisters, and two sons had anophthalmia and preaxial polydactyly in the right hand. Cytogenetic analysis was done for the proband and two of his sons, one of whom was affected. Another male child was affected but was not available for cytogenetic analysis. Karyotypes of both affected individuals showed deletion on long arm of 14q22q23. Literature review shows four cases of anophthalmia with extra ocular anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…This cooperation, together with the observation that Lhx2 and Pax6 regulate Six6 expression in mammals (Tetreault et al, 2009), constitutes a starting point towards the full identification of the transcriptional network controlling mammalian Six6 function. This, in turn, might help define the molecular causes of human inborn eye defects such as anophthalmia, microphthalmia and coloboma, which have been associated with genetic alterations of the SIX6 locus (Ahmad et al, 2003;Gallardo et al, 1999;Gallardo et al, 2004).…”
Section: Research Articlementioning
confidence: 99%
“…This cooperation, together with the observation that Lhx2 and Pax6 regulate Six6 expression in mammals (Tetreault et al, 2009), constitutes a starting point towards the full identification of the transcriptional network controlling mammalian Six6 function. This, in turn, might help define the molecular causes of human inborn eye defects such as anophthalmia, microphthalmia and coloboma, which have been associated with genetic alterations of the SIX6 locus (Ahmad et al, 2003;Gallardo et al, 1999;Gallardo et al, 2004).…”
Section: Research Articlementioning
confidence: 99%
“…Chromosome rearrangements involving the 14q22q23 region are rare with only a few interstitial deletions and one interstitial duplication reported (Bennett et al, 1991;Elliott et al, 1993;Lemyre et al, 1998;Ahmad et al, 2003;Nolen et al, 2006;Ou et al, 2008). All patients with interstitial 14q22q23 rearrangements show a common phenotype that includes bilateral anopthalmia, ear anomalies, microretrognathia, arched palate, facial asymmetry, and microcephaly.…”
Section: Discussionmentioning
confidence: 97%
“…A review of the literature showed five cases of anophthalmia with extraocular anomalies associated with 14q(q22q23) deletion: Bennett et al (1991), Elliott et al (1993), Phadke et al (1994), Lemyre et al (1998) and Ahmad et al (2003). Lemyre et al (1998), suggested that the region 14q22 is important for eye and pituitary development and human BMP-4 gene, a growth factor member of the TGF-b superfamily, maps to 14q22-23 and may play a role in pituitary and eye development.…”
Section: Discussionmentioning
confidence: 98%